Evolution of the Subsurface K‐Rich Brines in the Triassic Carbonates in the Sichuan Basin of China. Issue 5 (9th November 2017) - Zhou, Xun; Wang, Xiaocui; Han, Jiajun; Cao, Qin; Jiang, Changlong; Guo, Juan; Zhou, Haiyan
Abstract: Subsurface K‐rich brines are important mineral resources for fertilizer production while the evolution of such brines is poorly documented. In the Sichuan Basin in southwest China, they are found mainly in the Middle and Lower Triassic marine carbonate aquifers. Total dissolved solids of the brines range from 176 to 378 g/L and K concentrations, from 1.9 to 53.3 g/L. We found that the brines are mainly of Cl‐Na type, while Ba is absent in the brines. Comparison of the brine samples with both the trajectories of ions and the newly proposed trajectories of ion ratios of evaporated seawater suggests that the brines are enriched in Ca, Sr, Li, and I, depleted in SO4 and Mg, and neither enriched nor depleted in Cl and Na. These brines underwent four evolutionary periods: (1) deposition of marine rocks, (2) deposition of continental clastics, (3) tectonic deformation, and (4) rock erosion. Precipitation of salt minerals, dolomitization, sulfate reduction, and recrystallization during the first two periods are responsible for the enrichment and depletion of the chemical constituents of the brines. Extremely high K concentrations in two wells, both tapping the Middle Triassic Leikoupo carbonate aquifers, are attributed to the subsurface dissolution of potash salts during the migration of the brines to the anticlines formed during the third period in the Paleogene age. Saline and salty springs emanate from the outcropping carbonates in the river valleys in some anticlines in the eastern basin due to incongruent dissolution of the salt‐bearing carbonates during the fourth period. Abstract : Article impact statement : The evolution of K‐rich brines in the Sichuan Basin sheds light on similar occurrences of these brines important to fertilizer production.